Niobium pentoxide as a new filler for methacrylate‐based root canal sealers. (11th August 2012) - Leitune, V. C. B.; Takimi, A.; Collares, F. M.; Santos, P. D.; Provenzi, C.; Bergmann, C. P.; Samuel, S. M. W.
Abstract Aim To evaluate the influence of several niobium pentoxide (Nb2O5) concentrations on the radio‐opacity, flow, film thickness, microhardness and degree of conversion of an experimental root canal sealer. Methodology An experimental dual‐cured root canal sealer was produced with a methacrylate‐based comonomer blend. Nb2O5 was added at four different concentrations: 0, 80, 100 and 120 wt%. Radio‐opacity was evaluated according to ISO 6876 using a digital system (n = 5). Flow and film thickness were determined in accordance with ISO 6876 (n = 3). Microhardness was evaluated with 50 g for 15 s (n = 5). Degree of conversion was evaluated with FTIR immediately after photocuring and after 1, 7 and 14 days. The data were analysed using anova and Tukey's test. The degree of conversion over time was evaluated using RM‐anova (α = 0.05). Results The groups with 80 wt% and 100 wt% of filler showed no significant difference in radio‐opacity from that of equivalent 2 mmAl (P > 0.05). The addition of 120 wt% resulted in radio‐opacity values higher than 2 mmAl (P < 0.05). The flow was not significantly different amongst the different groups (P > 0.05). All groups had a film thickness of <50 μm (ISO 6876). All groups with Nb2O5 were associated with higher values of microhardness than the control group. The group with 0 wt% was associated with a higher degree of conversion at all times. All groups except those with 80 wt% had higher values for degree of conversion after 14 days than immediately after photocuring. Conclusion The addition of Nb2O5 increases radio‐opacity and microhardness; this material may be a promising filler for the production of a new endodontic sealer.